Sales Prediction Using Artificial Neural Network - Ilham Ariff, Mohammad Fadzli (2023)
In this research, an Artificial Neural Network (ANN) model was developed for the sales prediction. This research proposed the use of ANN for forecasting sales as an alternative to conventional forecasting techniques. The main objective of this research was to create an ANN model that can try to accurately forecast future sales using historical sales data. The proposed ANN model was trained using a backpropagation algorithm. The ANN consisted of multiple layers of artificial neurons. The sales dataset used in this study was collected from the Kaggle website. In conclusion, the proposed ANN model can assist business owners in making better decisions by forecasting future sales, identifying patterns and trends in the dataset.